The Demise of the Rights Issue - Hansen, Robert S. (Review of Financial Studies, 1988)
This article suggests that the lack of use of rights offerings in the United States, a phenomenon referred to as the equity underwriting paradox, can be explained by transaction costs. A sample of underwritten rights offerings provides support for the explanation. Firms making underwritten rights offerings paid lower underwriter fees but incurred significantly larger price drops just prior to the offering than did firms making underwritten offerings. Further analysis reveals that the underwritten-rights-offering price concessions are a form of transaction cost that is not found in underwritten public offerings.